Pilot Survey On The Conservation Of Historical Buildings In Malaysia - Kamal, Kamarul Syahril; Ab Wahab, Lilawati; Ahmad, A. Ghafar (2008)

(untitled)
Historic buildings basically represents the single most visible aspect of our past history and culture.